IMPLEMENTASI METODE SINGLE MOVING AVERAGE DALAM MEMPREDIKSI PENDAPATAN TOKO GOLDEN COMP BERBASIS WEBSITE - Ramadhani , Rizky; Sucipto , Hadi (Inovate, 2024)
Golden Comp Store is a shop that provides laptop repair services, buying and selling laptops, and computer accessories. Due to the constant changes and developments in electronic products, there is a risk that the products sold by the store may become outdated or unpopular among customers in a short period of time, leading to a decline in revenue. To address this issue, forecasting is used to determine future income so that the store can make better business decisions. SMA (Single Moving Average) is used as a method for income forecasting, and the forecast results are evaluated using MFE (Mean Forecast Error), MAD (Mean Absolute Deviation), MSE (Mean Squared Error), and MAPE (Mean Absolute Percentage Error). This research utilizes income data from 2021 to 2022. The SMA forecasting results using a 3-period yield better forecasts compared to other forecasting periods. In the 3-period period, it shows an MFE of Rp. 2,042,789, MAD of Rp. 3,223,519, MSE of Rp. 18,256,864,943,827, and MAPE of 17.63%. Keywords: Forecasting, Income, Single Moving Average.